STRESS AND PATHOPHYSIOLOGIC EFFECTS OF STRESS INDUCED CHRONIC CORTISOL (Scientific Conference on Multidisciplinary Studies, 2025)
Some people refer to cortisol as the stress hormone. The body produces cortisol to prepare the body to respond to a perceived danger or stressful situation. When facing sudden stress, the body enters an alarm reaction stage called the fight-or-flight response. This triggers a cascade of events to enable a person to act quickly. Stress raises the cortisol level in the body, triggering bodily changes that enable a person to react to the stressor.